2013
DOI: 10.1136/jnnp-2013-305395
|View full text |Cite
|
Sign up to set email alerts
|

Impulse control disorders in Parkinson's disease: decreased striatal dopamine transporter levels

Abstract: ObjectiveImpulse control disorders are commonly associated with dopaminergic therapy in Parkinson's disease (PD). PD patients with impulse control disorders demonstrate enhanced dopamine release to conditioned cues and a gambling task on [11C]raclopride positron emission tomography (PET) imaging and enhanced ventral striatal activity to reward on functional MRI. We compared PD patients with impulse control disorders and age-matched and gender-matched controls without impulse control disorders using [123I]FP-CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 34 publications
5
51
0
Order By: Relevance
“…This supports previous literature that DAT differences observed between those with and without an ICD is not simply an epiphenomenon of DRT use. 17 Furthermore, we performed additional analyses controlling for LEDD. In these models, changes from baseline to year 1 DAT availability in right caudate and mean total striatum were no longer significantly predictive of incident ICDs, suggesting that DRT initiation helped explain these relationships.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This supports previous literature that DAT differences observed between those with and without an ICD is not simply an epiphenomenon of DRT use. 17 Furthermore, we performed additional analyses controlling for LEDD. In these models, changes from baseline to year 1 DAT availability in right caudate and mean total striatum were no longer significantly predictive of incident ICDs, suggesting that DRT initiation helped explain these relationships.…”
Section: Discussionmentioning
confidence: 99%
“…15 16 17 Dopamine transporter (DAT) imaging may reveal early biomarkers predictive of ICD risk, as decreased DAT availability has been associated with both prevalent 17 and incident 18 ICDs in small, preliminary studies.…”
Section: Introductionmentioning
confidence: 99%
“…However, another study in patients with ICD who were on their regular dopaminergic drugs showed a reduction of DAT density in the right striatum (putamen and caudate), although no specific analysis was undertaken in the ventral striatum (Voon et al, 2014). Reduced DAT availability in the right striatum (ventral striatum, anterodorsal and posterior putamen) in drug-naive PD patients who developed ICD after the initiation of dopaminergic treatment has also been reported (Vriend et al, 2014).…”
Section: Pathophysiology Of Icd and Lid In Pdmentioning
confidence: 93%
“…The available data show that DAT is reduced in the ventral striatum, both bilaterally or in the right hemisphere (Vriend et al, 2014), and even in the whole right striatum (Voon et al, 2014) of patients with ICD or who were at risk of ICD. These data are intriguing as the right hemisphere has been shown to be more involved in "response inhibition network" (Aron et al, 2004), a fact that could be relevant to the pathophysiology of ICD.…”
Section: Pathophysiology Of Icd and Lid In Pdmentioning
confidence: 97%
“…Various approaches have been used to study the neurobiological underpinnings of impulse control disorders in Parkinson's Disease, including radiotracers, drug manipulations, and neuropsychological tasks (for excellent review see Napier et al 2015). For example, in a radioligand imaging study in patients with Parkinson's Disease, patients with concurrent impulse control disorders showed significantly lower binding of striatal dopamine receptors (Voon et al 2014b). In all, behavioural addictions in patients with Parkinson's Disease appear to be linked with dysregulation of striatal dopamine pathways, supporting involvement of reward circuitry in the manifestation of these disorders more widely.…”
Section: Parkinson's Disease and Medications: Broader Implications Fomentioning
confidence: 99%